2009
DOI: 10.1016/j.ajog.2009.06.069
|View full text |Cite
|
Sign up to set email alerts
|

Does frank diabetes in first-degree relatives of a pregnant woman affect the likelihood of her developing gestational diabetes mellitus or nongestational diabetes?

Abstract: Objective To examine the associations between patterns of family histories of diabetes and a history of gestational diabetes (hGDM). Study Design Parous women participating in the Third National Health and Nutrition Examination Survey (n=4566) were classified as having hGDM only, diagnosed diabetes, or neither. Family history of diabetes was categorized as: maternal-only, paternal-only, biparental, and sibling-only. The covariate-adjusted prevalence and odds of having hGDM were estimated. Results Compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 18 publications
4
18
1
Order By: Relevance
“…In our study an association between higher parity and GDM was not found to be statistically significant and this was inconsonance with the study done Rajput R et al and Jang et al 24,31 However in few studies higher parity has been found to be associated with higher prevalence of GDM. 19,25 In our study women had higher chances (odds) of having GDM who had family history of diabetes mellitus (OR: 25) and past history of GDM (OR: 30) and this association was found to be statistically significant.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…In our study an association between higher parity and GDM was not found to be statistically significant and this was inconsonance with the study done Rajput R et al and Jang et al 24,31 However in few studies higher parity has been found to be associated with higher prevalence of GDM. 19,25 In our study women had higher chances (odds) of having GDM who had family history of diabetes mellitus (OR: 25) and past history of GDM (OR: 30) and this association was found to be statistically significant.…”
Section: Discussioncontrasting
confidence: 86%
“…Similar observation was reported by other studies conducted elsewhere. [25][26][27]31,32 In our study women had higher chances (odds) of having GDM who had past history of macrosomia (OR: 60) and past history of abortions (OR: 24) and this association was found to be statistically significant. Similar observation was reported by Jindal et al and Dixon DRD et al 33,34 …”
Section: Discussionmentioning
confidence: 53%
“…Family history of DM has been reported to be associated with higher chances of developing GDM. 29 A significant association between history of GDM in previous pregnancy and development of GDM in index pregnancy was seen in present study.…”
Section: Discussionsupporting
confidence: 71%
“…(12,13,14,18) Seshiah et al (13) observed a significant association between the family history of diabetes mellitus and the occurrence of GDM in pregnancy. In the present study, 60% of women with GDM had a family history of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%